THE USE OF CODE MIXING IN TWEETS BY KPOP FANS IN TWITTER - Sylvia Dwiyota (STBA Prayoga Padang, 2018)
Code mixing is spreading all over the world because of the influence of globalization and social media. One of social media that takes role in code mixing daily use is Twitter. The writer conducted a research about code mixing in tweets by KPOP fans in twitter which shows the use of code mixing. The writer found out three types and six functions of code mixing that were used by KPOP fans in their tweets. The types were insertion, alternation, and congruent lexicalization. Meanwhile, the functions that were applied by KPOP fans in their tweets were to build social situation, to communicate with particular participant, to share ethnicity, to express idea easily, to create sense of humor, and to express disapproval.